Hydrochemistry Assessment of Surface and Groundwater Quality Using GIS and a Heavy Metal Pollution Index (HMPI) Model in a Hawija area, Kirkuk, north Iraq - Al-Hamdany, Ahmed H.; Al-Tawash, Balsam S.; Al-Jumaily, Hassan A. (Iraqi Journal of Science, 2025)
The Heavy Metal Pollution Index (HMPI) has been used to assess the quality of surface and groundwater drinking water in the Hawija region, where residents use groundwater for drinking. Forty groundwater samples were collected from the Hawija region's wells and analyzed in the Acme Laboratories in Canada. The results of this study were compared with the Environmental Protection Agency's (EPA) and the World Health Organization's (WHO) classification of water quality and its suitability for different uses. Five samples (12.5%) had low pollution levels during the low flow season, 26 samples (65%) had medium levels, and nine samples (22.5%) had high levels. Thirty samples, a mean of 75% of the total groundwater samples obtained during the high flow season, were rated as having low pollution, while ten samples (25%) were rated as having medium pollution. This shows that a large portion of the groundwater samples in the study area are impermissible for human consumption. In the low-flow season, the HMPI values ranged from 8.38 to 148.68, with a mean of 32.43 in the high-flow season, they ranged from 3.55 to 29.23, with a mean of 8.54. The HMPI values of surface water ranged from 3.75 to 77.64 and had a mean of 26.101 during the low-flow season, whereas they varied from 4.19 to 26.35 and had a mean of 11.25 during the high-flow season.